For a better adjuvant strategy for resected lung cancer—lessons from treatment failure patterns of the ADJUVANT trial (CTONG 1104) - Suda, Kenichi (Translational Lung Cancer Research; Vol 8, Supplement 4 (December 31, 2019): Translational Lung Cancer Research, 2019)
Surgical resection is a mainstay treatment for most patients with early-stage non-small cell lung cancer (NSCLC). With the recent improvements in the 5-year survival rates after lung cancer surgery (1), many thoracic surgeons are becoming interested in less invasive surgical techniques, such as sublobar resection for smaller NSCLC (2) or robotic (3) and uniportal (4) approaches to reduce the invasiveness of the chest wall.